The Effect of Online Gambling on Mental Health: Study on Teenagers in Panimbang District, Banten - Sidiq, Fahmi; binti Abdullah Suhaimi, Nurnisaa; Kalfin (International Journal of Health, Medicine, and Sports, 2024)
This study aims to evaluate the effect of online gambling on mental health in a group of teenagers in Panimbang District, Banten. The research was conducted to understand the impact of online gambling activities on the mental well-being of teenagers, focusing on factors such as stress, anxiety, depression and impulsive behavior. Survey and interview methods were used to collect data from selected samples, which included teenagers aged 15-19 years who were involved in online gambling activities. The results of this research indicate that engaging in online gambling has a negative impact on the mental health of adolescents in Panimbang District. Respondents who were involved in online gambling tended to experience higher levels of stress and anxiety than those who were not involved. Apart from that, the level of depression was also found to be higher in the group of teenagers who were involved in online gambling. This research also shows a positive correlation between online gambling activities and impulsive behavior. Teenagers who engage in online gambling tend to exhibit higher levels of impulsive behavior, which can impact their decisions in everyday life. These findings underscore the importance of awareness of the negative impact of online gambling on adolescent mental health. Preventive and intervention steps need to be taken to reduce the risk of these negative impacts.